External-World Skepticism in Classical India: The Case of Vasubandhu - Mills, Ethan (2017)
The Indian Buddhist philosopher Vasubandhu (c. 400 ce) has seldom been considered in conjunction with the problem of external-world skepticism despite the fact that his text, Twenty Verses, presents arguments from ignorance based on dreams. In this article, an epistemological phenomenalist interpretation of Vasubandhu is supported in opposition to a metaphysical idealist interpretation. On either interpretation, Vasubandhu gives an invitation to the problem of external-world skepticism, although his final conclusion is closer to skepticism on the epistemological phenomenalist interpretation. The article ends with reflections on what light Vasubandhu might shed on the issue of whether skepticism is a natural problem in epistemology as well as why, despite Vasubandhu, the skeptical problem was not a central issue in the later Indian tradition.
Keywords: Skepticism -- external world -- Indian philosophy -- Buddhist philosophy -- Vasubandhu